Price Markup in Property Purchase: A Legal Perspective on The Risk of Default and Decrease in Property Value at Auction - Wijaya, I Ketut Reksa; Yasa, Putu Gede Arya Sumerta; Bagiastra, I Nyoman (IJBLE Scientific Publications Community Inc., 2024)
Loans or credit are a commonly used financing model for new and existing businesses. The amount of credit granted is determined by the collateralized assets. However, problems often arise when the property used as collateral turns out to be valued below expectations. This occurs because property buyers become victims of price markup crimes. This study focuses on defining the boundaries of this crime in cases of price markup and the legal protections that can be provided to victims of property price markup. Consequently, the general public can avoid the risks of falling victim to such fraudulent schemes. This study delves into the intricacies of price markup crimes, aiming to delineate clear boundaries and legal protections for victims. By shedding light on these issues, we aim to empower the general public with knowledge to recognize and mitigate the risks associated with fraudulent schemes. Through a comprehensive understanding of the legal framework surrounding property price markups, individuals can make informed decisions and safeguard themselves against potential exploitation in property transactions. Ultimately, this research endeavors to foster transparency and accountability in the property market, fostering a fair and equitable environment for all stakeholders involved